2012
DOI: 10.1155/2012/150839
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Effectiveness of a 3-Week Balneotherapy Program for the Treatment of Overweight or Obesity

Abstract: Objective. To assess the one-year effectiveness on weight loss of a 3-week balneotherapy program (BT). Method. A Zelen double consent randomised controlled trial to compare one-year BMI loss between a 3-week BT program versus usual care (UC) for overweight or obese patients (BMI: 27–35 kg/m2), associated or not with a dietary motivational interview (DMI) during the follow-up, using a 2 × 2 factorial design. Main analysis was a per protocol analysis comparing patients attending BT to patients managed by UC, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It may also be necessary to combine ITW with more complex therapies such as spa therapies. A 3-week Zelen double consent randomized controlled trial ( N = 257) in France [ 27 ] found that a complex spa therapy with ITW (daily bubble bathing, water manual massages, mud therapy, water pool exercise, drinking of mineral water, nutrition and physical activity counseling) significantly reduced BMI (mean BMI loss after 14 months follow-up was 1.91 kg/m 2 [95 % CI: 1.46; 2.35]; P < 0.001). In a randomized, controlled trial from Poland [ 28 ] 50 overweight and obese patients (BMI = 43.8) presented a significant weight reduction with an average loss of 7 % of their initial weight and other CVRF such as total cholesterol, LDL-cholesterol, triglycerides and blood glucose after a 3-week spa therapy consisting of 15 daily mineral (4 % NaCl) thermal baths (31.0 °C) in a swimming pool and mud packs and a 1000 kcal diet.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be necessary to combine ITW with more complex therapies such as spa therapies. A 3-week Zelen double consent randomized controlled trial ( N = 257) in France [ 27 ] found that a complex spa therapy with ITW (daily bubble bathing, water manual massages, mud therapy, water pool exercise, drinking of mineral water, nutrition and physical activity counseling) significantly reduced BMI (mean BMI loss after 14 months follow-up was 1.91 kg/m 2 [95 % CI: 1.46; 2.35]; P < 0.001). In a randomized, controlled trial from Poland [ 28 ] 50 overweight and obese patients (BMI = 43.8) presented a significant weight reduction with an average loss of 7 % of their initial weight and other CVRF such as total cholesterol, LDL-cholesterol, triglycerides and blood glucose after a 3-week spa therapy consisting of 15 daily mineral (4 % NaCl) thermal baths (31.0 °C) in a swimming pool and mud packs and a 1000 kcal diet.…”
Section: Discussionmentioning
confidence: 99%
“…There are many methods used such as diet treatments, exercise treatments, drug treatments, and surgical interventions (Ricci et al 2016). These treatments include balneotherapy (Fioravanti et al 2015a;Firszt-Adamczyk et al 2016;Hanh et al 2012;Jokic et al 2018;Matsumoto 2018;Olah et al 2011;Rapolienė 2016;Rosc et al 2015), which traditionally involves immersion in mineral and/or thermal waters from natural springs, but may interchangeably be defined as balneological interventions with natural gases (CO 2 , sulfur and radon, etc. ), peloids (mud) and other traditional remedies (for example, hay), whereas hydrotherapy generally employs normal tap water for medical treatment (Fioravanti et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, it would be therefore termed "balneotherapy" (Gutenbrunner et al 2010) the treatment of mild CHF (Michalsen et al 2003) and hypertension (Jacob and Volger 2009); (4) balneotherapy in the treatment of atopic dermatitis (Farina et al 2011), psoriasis (mud therapy) (Costantino 2008a;Costantino and Lampa 2005;Delfino et al 2003), chronic venous insufficiency (Carpentier and Satger 2009), symptomatic varicosis (Mancini et al 2003), overweight/obesity (Hanh et al 2012), chronic inflammatory gynaecological disorders (Zambo et al 2008) and generalized anxiety disorder ( Dubois et al 2010); (5) aquatic exercise in the treatment of CHF (Cider et al 2003); and (6) spa therapy in the treatment of Parkinson's disease (Brefel-Courbon et al 2003). Most of the 22 uncontrolled studies report significant within-group improvements over time.…”
Section: Respiratory Diseasesmentioning
confidence: 99%